Kesiapan Guru Dalam Integrasi Literasi Numerasi Pada Pembelajaran Kurikulum Merdeka - Hamida Puspita; Karlina Amelia; Nurfitriani Azami; Rahma Nur Siti Fatimah; Tia Citra Bayuni (Arfah BHMS Foundation, 2026)
This study aims to analyze and evaluate the level of teacher readiness in integrating literacy and numeracy as the main foundation in the learning of the Merdeka curriculum. Although the Merdeka curriculum requires critical and logical thinking skills through literacy and numeracy, its implementation in the field still faces challenges such as limited understanding of concepts by teachers, lack of relevant training, and difficulties in designing contextual learning. This gap indicates that teacher readiness is a crucial factor that needs to be examined. This research uses a quantitative approach with a descriptive survey research type. Data were collected through a Likert scale questionnaire distributed online. In addition to measuring the level of readiness, the study also focuses on identifying factors that influence it, such as teaching experience and school support, as well as effective strategies implemented by teachers. Research findings show that most teachers are well-prepared cognitively and affectively, but there are still weaknesses in practical skill readiness, particularly in designing teaching materials and applying contextual methods. Based on the research results, it is recommended to provide more structured numeracy literacy training, continuous professional mentoring, and strengthened school support to enhance teachers' readiness in optimally implementing the Independent Curriculum.